2019
DOI: 10.34297/ajbsr.2019.04.000772
|View full text |Cite
|
Sign up to set email alerts
|

Estrous Cycle Ratio as a Reproductive Index in the Rats

Abstract: This work is licensed under Creative Commons Attribution 4.0 License AJBSR.MS.ID.000772

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The estrus cycle ratio was used to predict the intervals of folliculogenesis, luteogenesis, and luteolysis. An increase in the ratio of the estrus cycle can indicate the follicular phase and delayed ovulation (Adeniyi & Agoreyo, 2019). The results of the data showed that the dose of 400 mg/Kg BW had a higher ratio than the control (P<0.05).…”
Section: Estrus Cyclementioning
confidence: 94%
See 1 more Smart Citation
“…The estrus cycle ratio was used to predict the intervals of folliculogenesis, luteogenesis, and luteolysis. An increase in the ratio of the estrus cycle can indicate the follicular phase and delayed ovulation (Adeniyi & Agoreyo, 2019). The results of the data showed that the dose of 400 mg/Kg BW had a higher ratio than the control (P<0.05).…”
Section: Estrus Cyclementioning
confidence: 94%
“…The vaginal smear were then examined with an Olympus Cx21 microscope (100x magnification) and photographs were made with Optilab and Images raster (Mohammed & Sundaram, 2018). Observations consisted of the phase of the estrus cycle, the total length of the estrus cycle, and the ratio of the estrus cycle (Adeniyi & Agoreyo, 2019). The estrus cycle ratio was calculated by dividing the number of proestrus and estrus phases by the number of metestrus and diestrus phases with the following formula:…”
Section: Observation Of the Estrus Cyclementioning
confidence: 99%
“…Biorhythms are periodic variations in physiologic events occurring within a time frame. Important attributes of biorhythms include orderliness, entrainability, selfsustenance, and endogeny [1,27,28]. Biorhythms that are completed in less than 24 hours are called ultradian rhythms (example is ultradian LH secretion).…”
Section: Photic Stress and Rhythmically Controlled Physiological Proc...mentioning
confidence: 99%
“…These patterns are influenced by external cues such as light, temperature, metabolic activity, and diet. Indiscriminate exposure to external cues affects the pattern of the rhythms [1][2][3]. For instance, light is necessary as an external cue to reset circadian pacemakers situated in the suprachiasmatic nucleus; indiscriminate exposure to light and photic stress will affect the functionalities of these pacemakers, causing alteration in the rhythmic pattern of gene expressions with attendant impairments in physiological functions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, light also influences body temperature and the reproductive cycle. Specifically, in rodents' study, exposure to light stress has been shown to lengthen the estrous cycle and estrous cycle ratio [2,3,14] and impairs body temperature rhythm [15]. Light exposure may also influence the activities of antioxidant enzymes.…”
Section: Effect Of Photic Stress On Autonomic Nervous Systemmentioning
confidence: 99%